Strategi Pengembangan Agrowisata Lebah Etno Kecamatan Mengwi Kabupaten Badung - SIALLAGAN, DEWI; SURYAWARDANI, I GUSTI AYU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
Development Strategy of Etno Bee Agrotourism in Mengwi Sub-District, Badung Distric. Agrotourism presents a potential source of income and supports the increase in agricultural products. Etno Bee Agrotourism is an agrotourism that focuses on beekeeping which is a quality honey-producing agrotourism in Badung Regency. The purpose of this study was to determine the internal (strengths and weaknesses) and external (opportunities and threats) factors of the development process of EtnoBee Agrotourism, to determine the main strategies for developing Etno Bee Agrotourism and to determine alternative strategies for developing Etno Bee Agrotourism peaks based on analysis SWOT. The main strategy for this type is market penetration and product development. The good quality of honey and the increasing demand for honey need to be maintained and even increased. The Alternative strategy is the S-O strategy by maintaining the quality of honey as a tourist object and attraction. Maintaining a friendly workforce, working with beekeepers and communities around agro-tourism. The S-T strategy is to take advantage of social media and provide discounted prices. The W-O strategy is to optimally develop facilities and arrangements and create attractive promotional content. The W-T strategy is to add unique facilities and objects and create typical Ethno Bee Agrotourism souvenirs.